Development of Transition Metal Nitrilotris(methylenephosphonate)-derived Electrocatalysts for Alkaline Water Electrolysis - Vílchez-Cózar, Álvaro; Pérez-Colodrero, Rosario Mercedes; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio (My University, 2025)
Transition metal phosphonates have emerged as promising precursors for durable and efficient electrocatalysts in alkaline water electrolysis (AWE) [1]. Through controlled pyrolysis conditions, these materials are converted into transition metal phosphides or polyphosphates with precisely tuned phase composition and morphology [2]. This process also results in heteroatom-doped carbon matrices, which contribute to enhancing the conductivity and preventing nanoparticle agglomeration. Therefore, the tunable chemistry of these precursors allows for the design of tailored P-containing catalysts with optimized catalytic performance for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). In this work, we report the synthesis and structural characterization of several divalent transition metal phosphonates and their corresponding bimetallic derivatives derived from the nitrilotris(methylenephosphonic) acid (NTMPA). These materials were employed as precursors for the preparation of metal tetraphosphonates (M2P4O12) and metal phosphides (MxP) through pyrolysis under N2 and (5%)H2-Ar atmospheres, respectively, at temperatures ranging from 500 to 800 ºC. Their electrocatalytic performance were thoroughly evaluated for the HER and OER, and benchmarked against noble metal-based reference electrocatalysts. To establish structureperformance relationships, pair distribution function (PDF) and differential PDF analyses were conducted to track the structural evolution and stability of the electrocatalysts during electrochemical reactions [3]. Finally, the most effective catalysts were integrated into AWE systems which, after catalyst loading optimization, achieved cell voltages and stability comparable to those of noble metal-based systems.

References [1] Y.-P. Zhu, Z.-Y. Yuan, H. N. Alshareef, ACS Materials Letters, 2, 582–594 (2020). [2] R. Zhang, S. M. El-Refaei, P. A. Russo, N. Pinna, Journal of Nanoparticle Research, 20, 146 (2018). [3] Á. Vílchez-Cózar, R. M. P. Colodrero, M. Bazaga-García, D. Marrero-López, S. M. ElRefaei, P. A. Russo, N. Pinna, P. Olivera-Pastor, A. Cabeza, Applied Catalysis B: Environmental, 337, 122963 (2023).
Acknowledgments This work was supported by the Spanish Ministry of Economy, Industry and Competitiveness (projects PID2019-110249RB-I00, TED2021-129836B-I00 and PID2023-148883OB-I00, and the student grant PRE2020-094459).
Keywords: Electrocatálisis; Compuestos organofosforados; Electrocatalysis; Metal phosphonates; Oxygen evolution reaction; Hydrogen evolution reaction; Alkaline water splitting